Bioassays quantifying the lytic capabilities of various concentrations of goniodomin congeners (GDA, GDB, GDC, GDA-seco acid) on the cryptophyte Rhodomona salina - Kristof Möller; Urban Tillmann; Francesco Porreca; Bernd Krock; Florian Koch; Cédric Léo Meunier (PANGAEA, 2024)
The cryptophyte Rhodomonas salina was subjected to various concentrations of goniodomin congeners (GDA, GDB, GDC, GDA-seco acid) for 3, 24 or 48 h. Then, the percentage of intact R. salina cells was quantified microscopically. This dataset comprises all cell counts from the R. salina bioassays used to construct dose-response curves. The experiments were carried out between April 27–29, 2021 and March 20–22, 2024 in the laboratories at the Alfred-Wegener-Institute in Bremerhaven, Germany.